Malay-Indonesian Traditional in Shaping A “Worldwide” of Natural Healing: An Analysis for Women Health Maternity Using Herbs of Familia Zingiberaceae - Nawawi, Nur Faizzati; Nurulwahidah Fauzi; Khalijah Awang; Muhammad Widus Sempo (Maʿālim al-Qurʾān wa al-Sunnah, 2017)
Beauty and health care generally get special attention in the tradition of women in the Malay-Indonesian world. It’s proven through a practice of disease treatments and the daily diet that is very closely related to the use of herbs in the natural environment around them. The study found that there are various beauty tips and treatment of disease spread in public life until then it becomes known that is written with the purpose to pass their knowledge to the next generation. This study also aims to explain some of the main objectives, (1) to review the idea and the perspective of the women of Malay-Indonesian archipelago in the enculturation of application of herbs and plants in their daily lives, (2) to identify the herbs and plants of Zingiberaceae family used by women during confinement as classified in the Manuscripts MSS 1653 and MSS 2502 “Kitab Tibb”, (3) to investigate the methods used in treating women after giving birth and analyzes nutrition herbs mentioned in the provision of health nutrition and medicine that also known as “jamu”. The study found that herbal practice among the Malay community such as ginger, Zingiber zerumbet, turmeric and cekur (kaempferia galanga) frequently used by women during confinement because a quick cure and nutritionally healthy, thus it provenly help them to return the body to the best stage of health. These health practices need to be expanded its understanding in the community so that it is not lost in the tide of modernity, we have today.